Risk preferences and development revisited: A field experiment in Vietnam - Ferdinand M. Vieider; Nghi Truong; Peter Martinsson; Pham Khanh Nam; Peter Martinsson (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2013)
We obtain rich measures of risk preferences of poor farmers in Vietnam, and estimate structural models that capture risk preferences over different probability levels and across different domains (gains and losses). The results break radically with the previous literature on risk preferences, in developed and developing countries alike. Far from being particularly risk averse, our Vietnamese farmers are on average risk neutral. At the same time, we find our preference measures to perform well at predicting behavior, from the purchase of lottery tickets to risk management on the farm. We also find strong direct evidence of a risk-income paradox. While risk aversion is strongly decreasing in income within our farmer subject population, our Vietnamese farmers are significantly less risk averse than subjects in Western countries according to measurements obtained using the same decision tasks and procedures.
Keywords: C93; D03; D80; O12; 330; risk preferences; development; external validity